Pengaruh Daya Ledak Tungkai, Keseimbangan dan Tinggi Badan terhadap Kemampuan Lompat Jauh pada SMP Negeri 2 Bolupoddo - Irvan Mustafa (UNIVERSITAS NEGERI MAKASSSAR, 2022)
ABSTRACTThis study aims to determine: The Effect of Limb Explosive Power, Balance and Height on Long Jump Ability at SMP Negeri 2 Bolupoddo. This research is a descriptive type of research that uses a